Accelerated thymopoiesis and improved T‐cell responses in HLA‐A2/‐DR2 transgenic BRGS‐based human immune system mice. Issue 6 (2nd April 2019) - Masse‐Ranson, Guillemette; Dusséaux, Mathilde; Fiquet, Oriane; Darche, Sylvie; Boussand, Maud; Li, Yan; Lopez‐Lastra, Silvia; Legrand, Nicolas; Corcuff, Erwan; Toubert, Antoine; Centlivre, Mireille; Bruel, Timothée; et al.
Abstract: Human immune system (HIS) mouse models provide a robust in vivo platform to study human immunity. Nevertheless, the signals that guide human lymphocyte differentiation in HIS mice remain poorly understood. Here, we have developed a novel Balb/c Rag2 −/− Il2rg −/− Sirpa NOD (BRGS) HIS mouse model expressing human HLA‐A2 and ‐DR2 transgenes (BRGSA2DR2). When comparing BRGS and BRGSA2DR2 HIS mice engrafted with human CD34 + stem cells, a more rapid emergence of T cells in the circulation of hosts bearing human HLA was shown, which may reflect a more efficient human T‐cell development in the mouse thymus. Development of CD4 + and CD8 + T cells was accelerated in BRGSA2DR2 HIS mice and generated more balanced B and T‐cell compartments in peripheral lymphoid organs. Both B‐ and T‐cell function appeared enhanced in the presence of human HLA transgenes with higher levels of class switched Ig, increased percentages of polyfunctional T cells and clear evidence for antigen‐specific T‐cell responses following immunization. Taken together, the presence of human HLA class I and II molecules can improve multiple aspects of human B‐ and T‐cell homeostasis and function in the BRGS‐based HIS mouse model. Abstract : MHC molecules are critical for T‐cell selection. To improve T‐cell function in human immune system (HIS) mice, human HLA‐A2 and HLA‐DR2 transgenes were expressed in BRGS hosts. Humanized BRGSA2DR2 HIS mice showed enhanced T‐cell development and improved antigen‐specific T‐ and B‐cell responses.